Knockin' on Employment's Door: The Power of Caseworker Beliefs on Job and Health Outcomes for the Long-Term Unemployed - Søren Albeck Nielsen; Michael Rosholm (Institute of Labor Economics (IZA), 2025)
This study examines the impact of caseworker beliefs on employment and health outcomes among long-term unemployed social assistance recipients in Denmark. Exploiting as-if random caseworker assignment, an instrumental variables approach, and a novel measure of "Caseworker Job Orientation", we estimate the effects of caseworkers' job beliefs regarding their clients. Results indicate that clients assigned to caseworkers with stronger innate job beliefs experience substantial improvements in employment rates, earnings, and educational enrollment. Additionally, positive effects on health are observed, particularly among clients with pre-existing health conditions. These findings underscore the role of caseworker attitudes in shaping client trajectories, offering policy insights into enhancing labor market re-entry strategies.
Keywords: J68; I38; J65; C26; C93; 330; health outcomes; employment outcomes; long-term unemployment; caseworker beliefs; social assistance